Somerville Economic Summit in the Coolidge Room in Ballou Hall. Photo 061 - Ko, Melody (Tufts Archival Research Center, 2008)
Somerville Economic Summit in the Coolidge Room in Ballou Hall. Among the speakers were President Lawrence Bacow and Somerville Mayor Joseph Curtatone.